Innovative Energy-Efficient Solutions for Sustainable Development in Nigeria's Construction Industry - Unegbu, Hyginus Chidiebere Onyekachi; Yawas, Danjuma S.; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (JURNAL MECHANICAL, 2024)
The construction industry in Nigeria, like many developing countries, faces significant challenges and opportunities in adopting energy-efficient technologies. This study provides a comprehensive analysis of the current state of energy-efficient technologies in Nigeria's construction sector, examining adoption rates, perceived barriers, benefits, and recommendations for enhancing energy efficiency. Data were collected from 50 survey respondents and 15 in-depth interviews with key stakeholders, including architects, engineers, policymakers, and construction managers. The findings reveal that solar panels, LED lighting, and energy-efficient HVAC systems are the most commonly adopted technologies. Regression analysis indicates that regulatory support and stakeholder awareness are significant predictors of technology adoption, while financial constraints, regulatory challenges, and a lack of technical expertise are primary barriers. The thematic analysis highlights the interplay between economic incentives, regulatory environments, and cultural attitudes in influencing adoption. Operational cost savings, enhanced environmental sustainability, and improved indoor environmental quality are identified as major benefits of adopting energy-efficient technologies. The study provides several recommendations, including strengthening regulatory frameworks, providing financial incentives, enhancing capacity-building programs, conducting public awareness campaigns, and improving supply chains for green materials. This research contributes to the understanding of sustainable construction practices in Nigeria and offers practical strategies for overcoming barriers to the adoption of energy-efficient technologies. The findings have important implications for policymakers, industry stakeholders, and researchers aiming to promote sustainability in the construction sector.